European Muslims Transforming the Public Sphere : Religious Participation in the Arts, Media and Civil Society. - Soliman, Asmaa (Routledge Studies in Religion, 2017)
"Anti-Muslim voices have become louder in many places in the midst of ongoing atrocities undertaken in the name of Islam. As a result, much of the creative participation of Western Muslims in the public sphere has become overshadowed. This tendency is not only visible in political discussions and the media landscape, but it is also often reflected in academia where research about Muslims in the West is predominantly shaped by the post 9/11 narrative. In contrast, European Muslims Transforming the Public Sphere offers a paradigm shift. It puts forward a new approach to understanding minority public engagement, suggesting that we need to go beyond conceptualisations that look at Muslims in the West mainly through the minority lens. By bringing into dialogue minority-specific and non-minority specific concepts, the book offers a relevant complement.?Using young German Muslims engaged in media, the arts and culture and civil society as ten case studies, this book utilises the concepts of counterpublics and participatory culture to re-examine Muslims' engagement within the European public sphere. It presents a qualitative analysis, which has resulted from two years of ethnographic fieldwork and participant observation, in-depth interviews and primary source analysis of material produced by the research participants.?This book is a unique insight into the outworking of multiculturalism in Western Europe. It illustrates the many-sidedness of young Muslims' public contributions, revealing how they transform European public spheres in different ways. Therefore, it will be a vital resource for any scholar involved in Islamic Studies, the Sociology of Religion, Religious Studies, Cultural Studies and Media Studies."--Provided by publisher